Analisis Manajemen Waktu Belajar Siswa Ditinjau dari Jenis Kelamin - Yesi Amelinda; Dania Hasanah; Nova Tri Wulan Wahyu Ningsih; Suci Dinaria; Ramadhan Ramadhan; Yusuf Hartono; Khadijah Lubis (Lembaga Pengembangan Kinerja Dosen, 2026)
Education is a fundamental element in an individual's life that aims to optimize human potential across cognitive, affective, and psychomotor domains. This research is motivated by the importance of students' ability to manage their study time effectively to support optimal learning outcomes. The purpose of this study is to describe and compare students' study time management based on gender. This study used a descriptive comparative method, with a sample of several eighth-grade students at Islamic Boarding School X. Data were collected using a Likert scale instrument, then analyzed using descriptive techniques and an independent-samples t-test using the (Jeffreys’s Amazing Statistics Program) JASP application. The results indicate that several students are able to manage their study time well. Furthermore, no significant differences were found between male and female students in managing their study time. These findings indicate that the ability to manage study time is relatively even and is not influenced by gender.